An extensive review on quantum computers. (December 2022) - S, Nandhini; Singh, Harpreet; N, Akash U
Highlights: Quantum Error Correction (QEC) secured quantum data from decoherence and quantum noise. Quantum key distribution developed an information-theoretically safe solution for key commerce. Quantum computers illustrated very efficient and tremendously fast. Qiskit converted programming language to quantum machine language. Abstract: Quantum Computing is a rapidly arising innovation that tackles the laws of quantum mechanics to take care of issues excessively complex for already available classical computers. The development of quantum computers is the most remarkable achievement in the field and legacy of quantum computers. For instance, an already available classical computer can represent any number between 0 and 255 using just eight bits. However, a quantum computer can simultaneously represent all 256 numbers between 0 and 255 with just eight qubits. More numbers could be represented by a few hundred entangled qubits than there are atoms in the universe. There are many quantum computers available such as quantum circuit models, quantum Turing machine, adiabatic quantum computer, one-way quantum computers, and various quantum cellular automata. D-wave quantum computers have been available for more than eight years which use a process called quantum annealing to search for solutions to a problem. IBM, Microsoft, Google, Intel, and NASA and various universities around the globe have engaged themselves in the development of quantum computers and their applications. This paper presents the fundamental ideas of quantum computing and portrays notable quantum applications for non-physicists. The ongoing status of the improvements in quantum computers is likewise introduced.